Meen Galah Educational Intervention In Transformative Pedagogy: Revitalizing Local Wisdom To Strengthen Children's Mental Health - Kurnia Rahmayanti; Rahmad Alimin; Juleka Juleka; Anshar Iqlima; Husnul Khotimah (Jurnal Mamangan, 2025)
Children’s mental health has become a critical issue in education due to the rise of various psychosocial problems influenced by shifts toward a digital lifestyle and a decline in community-based social activities. On the other hand, the use of local wisdom as a tool for mental health interventions remains relatively limited. This study aims to analyze the effectiveness of the Meen Galah Education intervention within a transformative pedagogy framework as an effort to strengthen the mental health of elementary school children. The study employs a quantitative approach with a one-group pretest-posttest quasi-experimental design. The study participants consisted of 23 fifth- and sixth-grade students from SD Negeri Kajhu, Aceh Besar, selected using purposive sampling. The intervention was conducted over six sessions by integrating the traditional Meen Galah game, critical reflection activities, and collaborative learning. Mental health data were measured using the Strengths and Difficulties Questionnaire (SDQ), which covers aspects of emotional problems, behavioral problems, hyperactivity, peer problems, prosocial behavior, and total difficulty scores. Data analysis was conducted using descriptive statistics, the Paired Sample t-test, the Wilcoxon Signed-Rank Test, and Cohen’s d effect size. The results of the study indicate that the intervention significantly reduced emotional problems (Z = -4.260; p < 0.001), behavioral problems (t = 8.47; p < 0.001; d = 0.935), hyperactivity (t = 9.73; p < 0.001; d = 1.199), peer relationship problems (t = 5.21; p < 0.001; d = 1.441), and total difficulty scores (t = 12.77; p < 0.001; d = 2.856). Additionally, prosocial behavior increased significantly (Z = -3.787; p < 0.001). These findings suggest that Meen Galah Education, based on transformative pedagogy, has the potential to serve as a contextual, locally-rooted, and sustainable mental health intervention model within the elementary education setting. This study reinforces the importance of revitalizing traditional games as a pedagogical medium that not only preserves culture but also supports children’s psychological well-being